KESEIMBANGAN AKHLAK INDIVIDUAL DAN SOSIAL SEBAGAI RESPONS TERHADAP KRISIS MORAL MASYARAKAT MODERN - Mayasari Maya; Halimah Halimah; Ali Maulida Maulida (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
The development of modern society, characterized by globalization and rapid technological advancement, has given rise to various challenges, particularly moral crises that affect both individual and social life. This study aims to analyze the relevance of balancing individual and social ethics in addressing these challenges. The research employs a qualitative method using a library research approach by examining various sources of literature related to Islamic ethics. The findings reveal that individual ethical values, such as sincerity, trustworthiness, honesty, and patience, need to be integrated with social ethical values, including mutual assistance, justice, tolerance, empathy, social responsibility, and courtesy. The integration of these two ethical dimensions plays a significant role in shaping individual character while fostering social harmony. Furthermore, such a balance contributes to the development of morally responsible individuals and communities capable of responding to contemporary social challenges. In conclusion, the balance between individual and social ethics serves as an essential foundation for overcoming the moral crisis of modern society and for creating a harmonious, ethical, and responsible social order.